REKONSTRUKSI FIQH AN-NIKAH BERPERSPEKTIF GENDER - Mufti Hasan (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Abstract: In the classical fiqh literature, there are many writings that show discrimination against women, one of whom is a discussion of marriage or fiqh an-nika> h}. Many things are considered unfair to women. That is the reason why it is necessary to do the reconstruction of the fiqh an-nika> h} by reading and maping the relationships of inequality of men and women seen from a gender perspective. Some of the concepts that need to reconstruction is the first, the definition of marriage, changed to be more progressive and remove the impression of women as sexual objects. Second, the rights of women in fiqh al-muna>kahat, which include: custody, the right of testimony, the right to choose a marriage partner, right to the dowry, right to food, clothing, and shelter (living) and the right of mu'a> Syarah bi al-ma'ru> f in sexual relations. Related to the concept of polygamy, an-Nisa> ' article 3 can not be understood as a form of polygamy suggestion, that surah merely provides permissibility information of polygamy under certain conditions and with the proviso that no lightweight. In the concept of divorce, divorce should be done with justice and democratic principles, and should be done before the court. Related to the concept of 'iddah and ih {da> d, so 'iddah should be interpreted as a form of worship that can not be rationalized (ghairu ma'qul), so 'iddah remain relevant in fi kulli zaman. While ih {da> d must be done in a more humane without having to lower the dignity of women. While the concept of nusyu> z, article about nusyu> z can not be read partially, the verse must be paired with other verses that speak about the order to be fair and mu'a> bi Syarah bi al-ma'ru> f. Kata Kunci: Rekonstruksi, Fiqh an-nika>h, Perspektif Gender